The Effect of Covid-19 Pandemic on Surgical Practice in Nigeria - Owolabi Dele Ojo; Toye Gabriel Olajide; John Alaba Obateru; Adegbiji Atilade Waheed (International Journal of Coronaviruses, 2022)
Background The COVID-19 pandemic has had significant impact on healthcare worldwide. Surgeons are at increased occupational risk of contracting COVID-19. The impact of the disease on surgical practice will continue to evolve. We assessed the impact of the disease on surgical practice and training in Nigeria. Method Survey questionnaire was designed, transcribed to Google form and electronically circulated online to surgeons practicing in Nigeria. Surgeons from various subspecialties from the six regions in Nigeria were included. Survey questions pertaining to pre-COVID-19 era surgical practices, impact on current practice and changes occurring in health facilities during this COVID-19 pandemic. Responses were collated and analyzed statistically. Results One hundred and nine (109) surgeons completed the survey, of which 2.8% were women. Majority (68.8%) of the respondents are in the consultant cadre, majority (86.2%) are working in public hospital, 88.1% running their SOPD, 81.7% have isolation wards in their centers, 66.1% have dedicated team for COVID-19 management. Only 48.6% of the frontline health workers have access to personal protective equipment (PPE), and 33.9% had formal training on the use of PPE. Only 11.0% were satisfied with level of preparation of the management. Elective cases were done only in 45% of respondents. 103(94.4 %) confirmed that the numbers of elective cases are less than pre Covid-19 period. Emergency cases were carried out by 93.6% of respondents. Only 1.8% of respondents carried out screening tests for their patients before embarking on emergency surgery. Conclusion COVID-19 has led to reduction in surgical outpatients, significant reduction in elective surgeries in Nigeria. Adequate PPE needs to be provided, there should be guidelines for safety for future. There should be adequate preparation should there be any pandemic in the near future.
Keywords: COVID-19